Pengaruh Penggunaan Teknologi Informasi dan Komunikasi terhadap Kinerja UKM di Kota Bandung pada Masa Pandemi Covid-19 - Indriani, Eni; Husnun Salma, Neng Debi Husnun Salma (Asosiasi Ahli Administrasi Indonesia, 2021)
In this study, researchers drew on the performance of SME employees in Bandung City during the pandemic. At Small and Medium Enterprises (SMEs) in Bandung, where employees use information and communication technology that is incompatible with their function, such as skills in applying computer and internet-based information and communication technology. The purpose of this study is to analyze the effect of information technology on the performance of SMEs in Bandung. The method used in this research is descriptive method with a quantitative approach using one variable. The data analysis used in this study was carried out by means of validity tests, reliability tests, classical assumptions (consisting of normality tests and heteroscedasticity tests), simple linear regression analysis, and simple correlation. The data methods used were questionnaires and literature study. The results showed that the variables of information and communication technology had an effect on the performance of SMEs.